TINGKAT PEMAHAMAN MASYARAKAT TERHADAP ASURANSI SYARIAH PADA MASYARAKAT DESA SUKA DAMAI KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Siti Nurmala Sari; Sissah Sissah; Efni Anita (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Comprehension is defined as understanding, opinion or absorption of the meaning of the material being studied. However, in this research it was found that peaceful village communities had very little or minimal understanding of sharia insurance. To understand a little about the existence of sharia insurance requires direct outreach from the company. So that there are obstacles and appropriate solutions to deal with this. In this research, a qualitative approach was used with 15 sources to find answers to existing problems. Of the 15 informants in the research, 4 informants understood, 3 informants had little understanding and 8 informants did not understand sharia insurance at all.